2022
DOI: 10.1111/dom.14734
|View full text |Cite
|
Sign up to set email alerts
|

Metformin‐induced vitamin B12 deficiency can cause or worsen distal symmetrical, autonomic and cardiac neuropathy in the patient with diabetes

Abstract: Metformin blocks the absorption of vitamin B12 through a mechanism that has not been established but could be because of interference with the calcium-dependent binding of the intrinsic factor vitamin B12 complex to the cubam receptor in the terminal ileum. The subsequent deficiency of vitamin B12 may cause or accelerate distal symmetrical and autonomic neuropathy in the patient with diabetes. Several observational studies and meta-analyses have reported a significant association between metformin utilization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 53 publications
(105 reference statements)
0
36
0
2
Order By: Relevance
“…It is important to increase water consumption and the number of small meals and avoid abrupt changes in body posture. The resting tachycardia characteristic of the worsened stage of vagal dysfunction in CAN may be treated with cardioselective (i.e., beta-1) beta-adrenergic antagonists to improve vagal function [ 19 , 29 , 30 , 41 ]. As CAN progresses, reduced sympathetic response occurs and provokes orthostatic hypotension [ 20 ], which is treated with approved drugs targeted at primary or neurogenic orthostatic hypotension, such as droxidopa, midodrine, clonidine, pyridostigmine, and fludrocortisone.…”
Section: Alternative Treatment Of Dm-cardiac Autonomic Neuropathymentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to increase water consumption and the number of small meals and avoid abrupt changes in body posture. The resting tachycardia characteristic of the worsened stage of vagal dysfunction in CAN may be treated with cardioselective (i.e., beta-1) beta-adrenergic antagonists to improve vagal function [ 19 , 29 , 30 , 41 ]. As CAN progresses, reduced sympathetic response occurs and provokes orthostatic hypotension [ 20 ], which is treated with approved drugs targeted at primary or neurogenic orthostatic hypotension, such as droxidopa, midodrine, clonidine, pyridostigmine, and fludrocortisone.…”
Section: Alternative Treatment Of Dm-cardiac Autonomic Neuropathymentioning
confidence: 99%
“…However, long-term therapy with metformin, an insulin sensitizer, was recently associated with CAN aggravation due to its interference in vitamin B12 absorption in diabetic patients. Vitamin supplementation is recommended for diabetic patients in biguanide therapy for over 5 years or with additional risk factors (advanced age, bariatric surgery, or anti-ulcer therapy) and may be combined with calcium supplementation [ 41 ].…”
Section: Alternative Treatment Of Dm-cardiac Autonomic Neuropathymentioning
confidence: 99%
“…We also did not collect information on hypoglycemic agents for diabetes. Metformin may influence the level of SUA and increase the risk of neuropathy [ 46 ]. Thirdly, the nerve conduction testing in our study could only reflect the functional status of large fibrous nerves of peripheral nerves but could not detect the small fibrous nerves.…”
Section: Discussionmentioning
confidence: 99%
“…Metformin inhibits calcium-dependent channels in the ileum, hence preventing the absorption of vitamin B12 in the ileum. Several studies have shown that extended use of metformin causes vitamin B12 insufficiency through this mechanism [11][12][13][14][15][16]. A severe deficit may cause significant neurological problems [17].…”
Section: Introductionmentioning
confidence: 99%